2007
DOI: 10.1107/s1744309107064615
|View full text |Cite
|
Sign up to set email alerts
|

Purification, identification and preliminary crystallographic studies of Pru du amandin, an allergenic protein fromPrunus dulcis

Abstract: Food allergies appear to be one of the foremost causes of hypersensitivity reactions. Nut allergies account for most food allergies and are often permanent. The 360 kDa hexameric protein Pru du amandin, a known allergen, was purified from almonds (Prunus dulcis) by ammonium sulfate fractionation and ionexchange chromatography. The protein was identified by a BLAST homology search against the nonredundant sequence database. Pru du amandin belongs to the 11S legumin family of seed storage proteins characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Almond proteins, including the major storage protein amandin, have been identified as allergens. Eight native almond ( Prunus dulcis ) allergens have been characterized according to their biochemical function as summarized in Table 1 [ 30 , 31 , 32 , 33 ]. However, only four, Pru du 3, Pru du 4, Pru du 5, and Pru du 6 (amandin) are recognized and included in the WHO−IUIS list of allergens [ 34 ].…”
Section: Almond Allergensmentioning
confidence: 99%
“…Almond proteins, including the major storage protein amandin, have been identified as allergens. Eight native almond ( Prunus dulcis ) allergens have been characterized according to their biochemical function as summarized in Table 1 [ 30 , 31 , 32 , 33 ]. However, only four, Pru du 3, Pru du 4, Pru du 5, and Pru du 6 (amandin) are recognized and included in the WHO−IUIS list of allergens [ 34 ].…”
Section: Almond Allergensmentioning
confidence: 99%
“…In addition to the type of thermal processing, treatment temperature can also influence immunoreactivity. Amandin, an 11S legumin, has structural characteristics of the cupin superfamily and exhibits 42% sequence homology with soy glycinin (Gaur, Sethi, & Salunke, ). Plumb et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the type of thermal processing, treatment temperature can also influence immunoreactivity. Amandin, an 11S legumin, has structural characteristics of the cupin superfamily and exhibits 42% sequence homology with soy glycinin (Gaur, Sethi, & Salunke, 2008). Plumb et al (1994) found upon heating between 80 and 90°C soybean glycinin (11S) immunoreactivity decreased (60%), however when the treatment temperature was above 92°C immunoreactivity increased (125%).…”
Section: Indirect Sandwich Elisamentioning
confidence: 99%
“…The determination of initial phases was done by molecular replacement using program MOLREP 39 under the CCP4 software suite of version 6.0 40 . The crystal structure of Pru du amandin (PDB ID: 3ehk) was used as a search model 41 . The structure was refined by rigid-body refinement followed by iterated cycle of restrained refinement for atomic parameters by using the program REFMAC 5.8 42 .…”
Section: Methodsmentioning
confidence: 99%